EVALUASI TINGKAT KEPUASAN MAHASISWA TERHADAP PELAYANAN PENDIDIKAN PADA AKADEMI KOMUNITAS NEGERI ACEH BARAT - Luthfi; Erliana, Hilma; Wulan Sari, Intan; Mustari, Andi (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Intense competition between universities requires educational institutions to emphasize educational and institutional quality in order to maintain existence and achieve excellence. The quality of educational services at higher education institutions is a key factor that influences the level of student satisfaction. As the main customer, student satisfaction with educational services reflects the institution's success in providing a quality learning experience. This research aims to evaluate student satisfaction with various aspects of educational services at the West Aceh State Community Academy. The method applied is descriptive quantitative with a survey involving all registered students. The research instrument is a questionnaire that covers aspects of teaching quality, academic facilities, administrative services and learning environment. Data were analyzed using descriptive statistics to describe the level of student satisfaction. The research results show that the majority of students are satisfied with the quality of the services provided, although there are several aspects that require improvement. The highest level of satisfaction was found in the tangibles and responsiveness aspects, while the reliability and empathy aspects also showed significant levels of satisfaction. Recommendations from this research include improving the quality of physical facilities, training for lecturers and administrative staff, as well as improving services based on student feedback. Improving the quality of educational services is expected to help institutions achieve their vision and mission in creating graduates who have competitive abilities, are able to compete, and are ready to face challenges in the world of work.